PENGARUH KUALITAS PELAYANAN TERHADAP WORD OF MOUTH DENGAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Survei pada Konsumen PT Sinar Mas Cabang Surakarta) - Erni Widajanti, Susi Widiyanti, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Sinar Mas is a provider of financing vehicle loans. Problem faced bycompanies today is the declining number of customers, due to the high competitionamong companies financing in Surakarta. The purpose of research is to analyze thesignificance of the impact of service quality on customer confidence. Analyze thesignificance of the influence of service quality and customers' trust in the word of mouthcustomers. Analyze customer confidence mediate service quality to the word of mouth.This study uses survey method, the type of data used quantitative and qualitative data,the data source used primary data and secondary data. The population in this study allcustomers of PT Sinar Mas Surakarta Branch-month period October 2016 to December2016. The number of samples in this study as many as 100 people, the samplingtechnique uses accidental sampling. Data collection methods used were questionnaires.Data analysis technique used to test the validity, reliability test, classic assumption test,and path analysis. In conclusion, there was a significant effect of service quality oncustomer confidence. There was a significant influence on the quality of service word ofmouth. There was a significant influence customers' confidence in the word of mouth.Trust mediates the effect of service quality on word of mouth.Keywords: service quality, customer trust, word of mouth.